2015
DOI: 10.1136/bjsports-2014-094387
|View full text |Cite
|
Sign up to set email alerts
|

Injection therapies for lateral epicondylalgia: a systematic review and Bayesian network meta-analysis

Abstract: Some commonly used injection therapies can be considered treatment candidates for lateral epicondylalgia, such as botulinum toxin, platelet-rich plasma and autologous blood injection, but corticosteroid is not recommended. Hyaluronate injection and prolotherapy might be more effective, but their superiority must be confirmed by more research. The peppering technique is not helpful in injection therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
69
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 57 publications
0
69
0
1
Order By: Relevance
“…Specific comparisons made by each investigation can be found in Data . The majority of studies found the treatment(s) studied were relatively effective in treating tendinopathy as assessed by pain and patient‐reported outcomes 29‐32,34‐37,40‐52,54 …”
Section: Resultsmentioning
confidence: 99%
“…Specific comparisons made by each investigation can be found in Data . The majority of studies found the treatment(s) studied were relatively effective in treating tendinopathy as assessed by pain and patient‐reported outcomes 29‐32,34‐37,40‐52,54 …”
Section: Resultsmentioning
confidence: 99%
“…A recent Bayesian network meta-analysis that compared different injection therapies for lateral epicondylitis showed a not significant trend towards better effect than placebo for BoNT-A [32]. …”
Section: Resultsmentioning
confidence: 99%
“…(7) Prolotherapy, autologous blood or botulinic toxin injections, and others in ltrative therapies are less studied and therefore not clearly supported by the current literature. (8)(9)(10) Stem cells might be an alternative in the future. (11) Platelet-rich-plasma (PRP) is nowadays widely used for tendinopathies, considered as safe, and currently supported by the strongest scienti c journals (12).…”
Section: Introductionmentioning
confidence: 99%